PENGUATAN PENDIDIKAN KARAKTER (PPK) MELALUI PEMBELAJARAN BAHASA INDONESIA DI SEKOLAH DASAR - Wicaksono, Andri; Saputra, Hendra (Lentera: Jurnal Ilmiah Kependidikan, 2021)
Strengthening Character Education has become a breath of fresh air for the implementation of education. Character has become an obligation to be fostered continuously and needs to be directed until it is actually on track. For this reason, students need guidance and direction regarding the path that must be taken in the present and in a reflective way for the future. With the introduction of character education and its strengthening in learning, students will be patterned and systematized their behavior in a direction that is in accordance with the norm. The end result is to become Indonesian people with noble character and in accordance with the spirit of the National Mental Revolution Movement.